2017
DOI: 10.1177/102490791702400201
|View full text |Cite
|
Sign up to set email alerts
|

Could Hong Kong Primary Schoolchildren be Taught to Perform Compression-Only CPR: A Pilot Study

Abstract: To evaluate whether Hong Kong primary schoolchildren could be taught to perform compressiononly CPR. Design: Prospective experimental trial Subjects: Primary schoolchildren of age 9-12 years old from different Cub Scout packs attended a 2 hour voluntary compression-only CPR training session between late 2014 and mid-2015. Main outcome measures: Cardiopulmonary resuscitation (CPR) knowledge in the format of pre-and post-test multiple choices questions (MCQ). Psychomotor skills assessment including correct hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A total of 43,754 students were included in the 96 studies (44 RCTs, 25 , 26 , 27 , 28 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 30 uncontrolled before/after studies 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 43,754 students were included in the 96 studies (44 RCTs, 25 , 26 , 27 , 28 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 30 uncontrolled before/after studies 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Of the 44 RCTs, only 13 directly compared practical vs. nonpractical training (n = 5) 28 , 51 , 55 , 62 , 67 , self-training vs. instructor-led training (n = 7) 28 , 32 , 34 , 51 , 55 , 61 , 67 or peer-training vs. instructor-led training (n = 5) 27 , 56 , 57 , 59 , 61 . We treated the remaining RCTs (n = 31) 29 , 54 , 56 , 21 , 22 , 25 , 26 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 59 , 60 , 61 , 62 as one arm cohorts and combined them with the uncontrolled before/after studies (n = 30) 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , …”
Section: Resultsmentioning
confidence: 99%
“…Some initiatives included free CPR training for taxi drivers, free first aid talks in local primary and secondary schools, research on CPR learning (Chung et al , 2010) and pet first aid. Another study further investigated whether Hong Kong children could be taught to perform compression only CPR (Cy et al , 2017). The result concluded that it was worthy of advocating compression only CPR to primary school children in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%